ÇALIŞMA VE GÖÇ: ÇALIŞ(MAY)AN GÖÇMEN KADINLAR - Adiloğlu, Selda (IJOPEC Publication Limited, 2018)
The concept of work which is evaluated through this study will be examined within the scope of after migration experiences of the women who have immigrated to Turkey because of the reasons as marriage. Turkish migrants who are from Macedonia and Kosovo are two migrant groups to whom will be focused in this article. The semi-structured interviews which were had with 55 Macedonian and Kosovan Turkish migrant women in Tekirdağ and Bursa executes the (non)working behaviours of the migrants in point and expectations and determinants that form this behaviours. Basic claim of this article is to show the earlier life experiences directly effects the new life style, on the other hand expectations and earlier family lifes shapes (non)working behaviours of migrant women. This article which evaluates labor migrations from more different point than the other studies will examine working behaviours of the migrants who got/didn’t get involved in work life after migration experience that caused by different reasons (as marriage) out of labor aims instead of examining migrants whose purposes in migration to get involved in work life. Thus, this study will reveal an aspect differently from the other studies that have discussed the migration and work phenomenon in the context of labor migrations.
EMPLOYMENT AND MIGRATION: (NON)EMPLOYED MIGRANT WOMEN
Keywords: Migrant women; Concept of working; Macedonian-Kosovan migrant woman